2016
DOI: 10.1371/journal.pbio.1002516
|View full text |Cite|
|
Sign up to set email alerts
|

LKB1 Regulates Mitochondria-Dependent Presynaptic Calcium Clearance and Neurotransmitter Release Properties at Excitatory Synapses along Cortical Axons

Abstract: Individual synapses vary significantly in their neurotransmitter release properties, which underlie complex information processing in neural circuits. Presynaptic Ca2+ homeostasis plays a critical role in specifying neurotransmitter release properties, but the mechanisms regulating synapse-specific Ca2+ homeostasis in the mammalian brain are still poorly understood. Using electrophysiology and genetically encoded Ca2+ sensors targeted to the mitochondrial matrix or to presynaptic boutons of cortical pyramidal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
163
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 153 publications
(170 citation statements)
references
References 75 publications
(91 reference statements)
6
163
1
Order By: Relevance
“…The genes driving the enrichment for these processes were STX1A , ABHD11 , and DNAJC30 , and this was consistent using either BrainSpan’s RNA-seq dataset or an independent exon array dataset from developmental human brains (Kang et al, 2011). This confluence of synaptic transmission and mitochondrial respiration ontologies is consistent with the high metabolic demand and necessarily coordinated calcium flux needed for proper neuronal excitation (Kwon et al, 2016). …”
Section: Resultssupporting
confidence: 53%
“…The genes driving the enrichment for these processes were STX1A , ABHD11 , and DNAJC30 , and this was consistent using either BrainSpan’s RNA-seq dataset or an independent exon array dataset from developmental human brains (Kang et al, 2011). This confluence of synaptic transmission and mitochondrial respiration ontologies is consistent with the high metabolic demand and necessarily coordinated calcium flux needed for proper neuronal excitation (Kwon et al, 2016). …”
Section: Resultssupporting
confidence: 53%
“…This result establishes that mitochondria do not display significant changes in their membrane potential during axon maturation in vitro . To test whether or not mitochondria are capable of importing calcium during AP-evoked release [16], we applied 100APs at 10Hz using a micropipette stimulation near the labeled axons and found that mitochondria in both immature and mature axons responded by importing calcium into their matrix on similar timescales (Figure S1D–G). We calculated the area under the curves (as an estimate of the ‘total charge transfer’) and found a small but significant increase in the amount of calcium imported by mitochondria in mature axons in vitro (Supplemental Figure 1G).…”
Section: Resultsmentioning
confidence: 99%
“…Some, but not all, synapses in many parts of the cerebral cortex turn over during the diurnal cycle due to the ultradian fluctuation of glucocorticoids, and interfering with that cycle by elevated glucocorticoids at the wrong time of day interferes with motor learning, like learning to play golf (Liston et al, 2013). The formation of new spines (Li et al, 2004), dynamic regulation of synaptic strength (Kwon et al, 2016; Sun et al, 2013), and terminal axon branching (Courchet et al, 2013). …”
Section: Glucocorticoids: Not Just “Stress”mentioning
confidence: 99%